Numerical simulation for fractional optimal control problems via euler wavelets - Dincel, Arzu Turan; Tural-Polat, Sadiye Nergis; Afacan, Mustafa Oguz (IOP Publishing Ltd, 2024)
This paper suggests employing Euler wavelets to provide a precise and effective computational approach for certain fractional optimal control problems. The primary objective of the approach is to transform the fractional optimal control problem defined by the dynamical system and performance index into systems of algebraic equations, which then can be readily solved using matrix techniques. Since Euler polynomials are employed to build Euler wavelets and since Euler polynomials have fewer terms than most of commonly used other polynomials to build wavelets, employing them for the numerical approach results in sparser operational matrices. The speed of the recommended numerical method is improved due to the fewer terms in Euler wavelet operational matrices. We obtain the corresponding systems of algebraic equations for state variable, control variable, and Lagrange multipliers (used to determine the essential conditions of optimality) by incorporating operational matrices of Euler wavelets. Subsequently, those systems of algebraic equations are solved to obtain the numerical solution. The suggested method's efficiency is demonstrated using a few typical examples. The suggested procedure is accurate and efficient, according to the results.
Keywords: euler wavelets (EWs); fractional optimal control problems (FOCPs); lagrange multiplier method; EW operational matrix; numerical solution; APPROXIMATION; OPTIMIZATION; MODEL; Physics